Functionalism of Sculpture in Architecture: A New Perspective on Art and Form (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
Sculpture and architecture have traditionally been separate, with sculpture serving as decoration. However, with the rise of modernism and functionalism in the 20th century, sculpture began to be seen as an integral part of architecture, not just as an ornament. Functionalism in architecture suggests that the form of a building should follow its function, and sculpture, in this context, serves both aesthetic and practical roles. Examples from architects like Antoni Gaudí and Le Corbusier show how sculpture enhances the functionality of buildings. Modern technologies, such as 3D printing and laser cutting, have further integrated sculpture into architecture, allowing for more complex and interactive designs. Today, sculpture in architecture continues to evolve, blending aesthetic and functional elements to create spaces that are both beautiful and practical.